Differential Allocation of Attention During Speech Perception in Monolingual and Bilingual Listeners - Astheimer, Lori B. (Lang Cogn Neurosci, 2015)
Attention is required during speech perception to focus processing resources on critical information. Previous research has shown that bilingualism modifies attentional processing in nonverbal domains. The current study used event-related potentials (ERPs) to determine whether bilingualism also modifies auditory attention during speech perception. We measured attention to word onsets in spoken English for monolinguals and Chinese-English bilinguals. Auditory probes were inserted at four times in a continuous narrative: concurrent with word onset, 100 ms before or after onset, and at random control times. Greater attention was indexed by an increase in the amplitude of the early negativity (N1). Among monolinguals, probes presented after word onsets elicited a larger N1 than control probes, replicating previous studies. For bilinguals, there was no N1 difference for probes at different times around word onsets, indicating less specificity in allocation of attention. These results suggest that bilingualism shapes attentional strategies during English speech comprehension.